Charlie's snow day - Drummond, Ree.; De Groat, Diane; Drummond, Ree. (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2013)
Charlie the basset hound enjoys a snowy day on the ranch.
"Based on the Charlie the ranch dog books by Ree Drummond, The Pioneer Woman and Diane deGroat"--T.p.
"1, beginning reading"--T.p.
"Guided reading level G"--Back cover.
1.6
K-3
Keywords: Ranch life -- Juvenile fiction; Basset hound -- Juvenile fiction; Dogs -- Juvenile fiction; Snow -- Juvenile fiction; Ranch life -- Fiction; Basset hound -- Fiction; Dogs -- Fiction; Snow -- Fiction; Ranch life -- Fiction; Basset hounds -- Fiction; Dogs -- Fiction; Snow -- Fiction; Ranch life -- Fiction; Basset hound -- Fiction; Dogs -- Fiction; Snow -- Fiction; Readers (Elementary)